2021
DOI: 10.1080/20477724.2021.1984726
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of MBL2 and NOS3 functional gene variants in suspected COVID-19 PCR (–) patients

Abstract: For COVID-19 (Coronavirus Disease-2019) cases, detecting host-based factors that predispose to infection is a very important research area. In this study, the aim is to investigate the MBL2 and NOS3 gene polymorphisms in COVID-19 patients with lung involvement, whose first nasopharyngeal PCR results were negative. Seventy-nine patients diagnosed with COVID-19 between April-June 2020 who were admitted to a university hospital, and 100 healthy controls were included.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In our study, the association of the 4a allele with the risk of severe COVID-19-associated pneumonia was determined. In contrast, in the study of Pehlivan et al no significant difference in the distribution of genotypes for the rs61722009 variant among patients diagnosed with COVID-19 (all patients had typical COVID-19 lung involvement in their initial CT) and healthy controls was found [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the association of the 4a allele with the risk of severe COVID-19-associated pneumonia was determined. In contrast, in the study of Pehlivan et al no significant difference in the distribution of genotypes for the rs61722009 variant among patients diagnosed with COVID-19 (all patients had typical COVID-19 lung involvement in their initial CT) and healthy controls was found [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 29 , 30 ] Noteworthily, 80% of diabetic patients die of thrombotic death, so F2 is also an important target for the prevention and treatment of diabetes. [ 31 ] Studies have found that polymorphisms in the NOS3 gene are closely related to susceptibility to COVID-19 [ 32 ] and susceptibility to vascular disease in patients with type 2 diabetes, [ 33 ] indicating this gene to be an important target for the treatment of both diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide is essential in COVID-19, as it develops inflammatory stress to prevent pulmonary hypertension [ 106 , 127 ]. Prooxidant eNOS enzyme is encoded by the NOS3 gene, which is highly polymorphic.…”
Section: Candidate Gene Studies Of Oxidative Stress Pathway In Covid-19mentioning
confidence: 99%
“…The A allele was higher in COVID-19 patients, whereas the B allele and the AB genotype were higher in individuals with negative tests. NOS enzyme catalyzes superoxide anion production and promotes nitric oxide synthesis [ 106 ].…”
Section: Candidate Gene Studies Of Oxidative Stress Pathway In Covid-19mentioning
confidence: 99%